Profile of women with cervical cancer attended for treatment in oncology center - Ruan Carlos Gomes da Silva; Amanda Cristina de Oliveira Silva; Adrya Lúcia Peres; Sibele Ribeiro de Oliveira
Abstract Objectives: to evaluate the sociodemographic, clinical, histopathological, cytopathological and microbiological profile of women with cervical cancer treated at Oncology Center in Pernambuco, located in the city of Caruaru-PE. Methods: a retrospective study was carried out to evaluate the medical records of women with cervical cancer treated for radiotherapy and/or chemotherapy between January 2014 and December 2016. For the analysis of variables, the absolute and relative frequencies were calculated. Results: there was a predominance of cases in the age range between 40 and 59 years (45.37%), non-white race/color (91.75%) and incomplete primary education (44.32%). Squamous carcinoma was present in 85.19% of the cases, with a moderately differentiated histological grade being the most common (53.41%). Most women underwent radiotherapy and associated chemotherapy (72.72%) and had 3 or more pregnancies before diagnosis (73.44%). Cytopathology has more frequently identified high-grade squamous intraepithelial lesion (HSIL) cases (45.83%) and cocci and/or bacilli (66.67%) were the most evident microorganisms. Conclusions: the results showed that the perimenopause age, low educational level, multiparity, cytopathologic result of HSIL and histopathological examination evidencing moderately differentiated squamous cell carcinoma were among the characteristics most related to cervical cancer in the population studied.